Review: Biological fertilization and its effect on medicinal and aromatic plants - KHALID ALI KHALID (Nusantara Bioscience, 2012)
Abstract. Khalid KA. 2012. Review: Biological fertilization and its effect on medicinal and aromatic plants. Nusantara Bioscience 4: 124-133. The need to increase food production in most developing countries becomes the ultimate goal to meet the dramatic expansion of their population. However, this is also associated many cases with a reduction of the areas of arable land which leaves no opinion for farmers but to increase the yield per unit area through the use of improved the crop varieties, irrigation, and fertilization. The major problem facing the farmer is that he cannot afford the cost of these goods, particularly that of chemical fertilizers. Moreover, in countries where fertilizer production relies on imported raw materials, the costs are even higher for farmer and for the country. Besides this, chemical fertilizers production and utilization are considered as air, soil, and water polluting operations. The utilization of bio-fertilizers is considered today by many scientists as a promising alternative, particularly for developing countries. Bio-fertilization is generally based on altering the rhizosphere flora, by seed or soil inoculation with certain organisms, capable of inducing beneficial effects on a compatible host. Bio-fertilizers mainly comprise nitrogen fixes (Rhizobium, Azotobacter, Azospirillum, Azolla or blue-green algae), phosphate dissolvers or vesicular-arbuscular mycorrhizas and silicate bacteria. These organisms may affect their host plant by one or more mechanisms such as nitrogen fixation, production of growth promoting substances or organic acids, enhancing nutrient uptake or protection against plant pathogens. Growth characters, yield, essential oil and its constituents, fixed oil, carbohydrates, soluble sugars and nutrients contents of medicinal and aromatic plants were significantly affected by adding the biological fertilizers compared with recommended chemical fertilizers.